Conformational disorder of a substituted polythiophene in solution revealed by excitation transfer - Grage, M. M.-L.; Pullerits, T.; Ruseckas, A.; Theander, M.; Inganäs, O.; Sundström, V. (Chemical Physics Letters, 2001)
Anisotropy and isotropic transient absorption decays of a polythiophene derivative in dilute solution have been measured and compared to calculated decays on Monte Carlo simulated polymer chains to obtain knowledge about the geometrical conformation of the polymer. The polymer chain conformations are generated by a partially correlated self-avoiding random walk. Excitation migration along the isolated chain is modeled assuming a hopping mechanism. This approach can be used to determine conformational disorder and possible realizations of the polymer chains in solution as well as the trapping time and migration length of the excitation.